Numerical comparison of aerodynamic performance between stationary and moving trains with varied-height windbreak wall under crosswind - Ru-Dai Xue; Xiao-Hui Xiong; Guang Chen; Xiao-Bai Li; Bin Liu (Alexandria Engineering Journal)
This paper investigates the impact of windbreak wall’s heights on the aerodynamic characteristics’ difference of trains between moving and stationary numerical simulation methods. The 1/8 scaled train model with windbreak wall at three heights under crosswind was simulated based on the IDDES turbulence model. The results found that the error of aerodynamic loads between two simulation methods increases with the elevation of the windbreak wall’s height with the largest value observed in the tail car. Comparing the time-averaged pressure on the train body in the two simulation methods, the most notable disparity manifests in the head car. The negative pressure around head car in stationary case is larger than that in moving case. For stationary simulation, the flow field is primarily influenced by the vortex structures generated at the end of the windbreak wall. In contrast, for moving simulation, the vortex structures on the leeward side of the train are predominantly formed by the detachment from the train’s top. In conclusion, the aerodynamic loads and flow field characteristics of the train exhibit noticeable discrepancies under two simulation methods, and the disparities increase with the elevation of the windbreak wall’s height.